WOUND INFECTIONS AFTER TOTAL MEDIAN STERNOTOMY – RISK FACTORS, MICROBIOLOGICAL ANALYSIS, PROPHYLAXIS AND TREATMENT METHODS - H. Stoev (Trakia Journal of Sciences)
Introduction. Median sternotomy represents a standard surgical access in cardiac surgery, despite the growing popularity of minimally invasive access. Posternotomy infections are a serious complication and are directly related to patients' survival in the short and long term. Despite prevention, their expression is still significant - from 0.5% to 6.8%, and associated hospital mortality rates range from 7% to 35%. Aims. Analysis of frequency, risk factors, microbiological agents, prevention options and surgical techniques for deep wound infections after open heart surgery for a 17 - year period. Materials and methods. For the period from October 2002 to June 2019, 146 (1.42% of 10,307 operated) patients were treated at the Cardiac Surgery Clinic at the University Hospital “St. Georgi "diagnosed with deep sternal infection. The study is a retrospective using data from medical records and hospital records. The Center of Disease Control (CDC) criteria were used to define deep sternal infections. Results. The sex ratio is 2.04: 1 – men: women. The average age for both sexes is 65.4 years. The average stay of patients in the intensive care unit was 5 days (from 0 to 46 days), and the average total hospital stay was 15.6 days (from 5 to 55 days). Early postoperative mortality was 13,7%. The most common risk factors were diabetes mellitus, obesity and emergency surgery. Conclusion. Cardiac surgery with total midline sternotomy is associated with a risk of developing mediastinitis. Despite the advances in cardiac surgery and the use of mini-invasive techniques, the rate of development of deep wound infections remains relatively high.